Determining the Lifespan of Hydrothermal Systems Using Thermochronology and Thermal Modeling. Issue 11 (29th October 2021) - Jess, Scott; Enkelmann, Eva; Grasby, Stephen E.; Fraser, Kelley
Abstract: The drive toward lower carbon emissions has led to a rise in global geothermal exploration. Hot springs are key exploration targets as they reflect active advection of thermal fluids derived from heating of meteoric waters circulating through the upper crust. However, establishing the timing of hot spring formation and the longevity of systems remain key knowledge gaps in our understanding of geothermal systems, such as how and when hydrogeologic conditions enable deep groundwater circulation to initiate. In this study, we demonstrate that a combination of multiple low‐temperature thermochronometers and finite element modeling can be used to determine the lifespan of the Canoe River Hot Springs flow system, British Columbia, Canada. Rocks adjacent to the hot spring show evidence of reheating because of thermal fluids, an effect absent in more distant samples. Hydrothermal modeling of both constant and episodic flow scenarios over different timescales highlights that the hot spring likely began flowing between 4 and 6 Ma. This timing of flow onset implies the hot spring's formation may be linked to partial melting at the base of the crust, associated with nearby volcanic activity that has increased heat flow across the region in the late Cenozoic. These results have significant implications for the exploration of geothermal energy systems and for understanding the conditions required to form hot springs across British Columbia. Plain Language Summary: Hot springs have become a target for geothermal energy exploration as the world continues to transition from fossil fuels to green energy. The emergence of hot water at spring outlets is seen as an indicator of both a thermal resource and a permeable pathway through rocks suitable for geothermal development. However, our understanding of how long hot springs have been active in each location is limited. The longevity of a geothermal system is important for modeling sustainable resource production and understanding how spring systems form. In this study we use temperature sensitive dating methods to determine how long the Canoe River Hot Springs, located in southwestern Canada, has been active to assist in geothermal energy exploration. The hot spring waters heat the surrounding rock, and our analysis allows the thermal history of a rock to be determined on geological time scales of >1 million years. Through the application rock dating and computer modeling we have been able to determine that Canoe River Hot Springs has been active for 4–6 million years. This study also provides an analytical workflow for determining how long other hot springs have been active, to the benefit of the geothermal industry. Key Points: Low‐temperature thermochronology is used to estimate the lifespan of a hot spring Combining fission track, (U‐Th‐Sm)/He, and finite element modeling can help determine when spring flow initiated Canoe River Hot Springs has likely been active since the late Miocene